Pain-Associated Diagnoses in Childhood Before the Diagnosis of Attention-Deficit/Hyperactivity Disorder: A Population-Based Study - Eugene Merzon; Eli Magen; Yaniv Levy; Shai Ashkenazi; Iris Manor; Abraham Weizman; Beth Krone; Stephen V. Faraone; Ilan Green; Avivit Golan-Cohen; Shlomo Vinker; Ariel Israel (Children)
Background: Pediatric pain significantly affects children’s lives, leading to school absenteeism, impaired social interactions, and psychological distress. The perception of sensory signals as pain is influenced by the brain’s noradrenergic system, and recent evidence suggests that chronic pain may impact cognitive functioning and emotional regulation. Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with alterations in the dopaminergic/noradrenergic systems, which could affect pain perception. Pain-associated conditions and frequent analgesic use in childhood may be linked to ADHD development and could serve as early indicators, yet data on this potential association remain limited. Study Aim: This population-based case-control study in Israel aimed to assess the prevalence of pain-related diagnoses prior to ADHD diagnosis in children aged 5 to 18. The study included children registered with Leumit Health Services (LHS) between 1 January 2006, and 30 June 2021. Children diagnosed with ADHD were compared to matched controls, selected based on age, gender, socioeconomic status, and other sociodemographic factors, who were never diagnosed with ADHD during the study period. Results: Children with ADHD (N = 18,756) and controls (N = 37,512) were precisely matched for sociodemographic characteristics. Individuals with ADHD exhibited significantly higher frequencies of diverse pain conditions, including those associated with illness [headache, earaches, and throat pain (odds ratios [OR] = 1.156 [95%CI 1.085, 1.232], 1.295 [95%CI 1.217, 1.377], and 1.080 [95%CI 1.019, 1.145], respectively; p < 0.01)] and injury [sprains and strains (OR = 1.233 [95% CI 1.104,1.376)]. Analgesics were more frequently purchased by individuals with ADHD, particularly paracetamol (OR = 1.194 [95%CI 1.152, 1.237], p < 0.001) and ibuprofen (OR = 1.366 [95%CI 1.318, 1.416], p = 0.001). Conclusions: This study highlights a potential connection between ADHD and pediatric pain. The elevated rates of pain diagnoses and analgesic usage among children with ADHD underscore the need for further research.